Briefly on the Expediency of Discussion Concerning the Publications of V.V. Gordienko on the Nature of the Earth’s Magnetic Field - В.І. Старостенко; V.P. Kobolev (Геофизический журнал)
The article discusses the need for a critical reassessment of modern conceptions regarding the Earth's magnetic field, particularly its sources, mechanisms of change and inversion, and configuration. Doctor of Geological and Mineralogical Sciences V.V. Gordienko, renowned for his comprehensive studies of magnetic anomalies and criticism of the plate tectonics hypothesis, considers existing explanations insufficient. Meanwhile, Doctor of Physical and Mathematical Sciences Ya.M. Khazan, in his detailed review, analyzes Gordienko’s article and highlights its contribution to geophysical science. The work of both scientists stimulates further research in the field of geophysics and holds significant value for the scientific community.